2013
DOI: 10.5513/jcea01/14.1.1220
|View full text |Cite
|
Sign up to set email alerts
|

Summary of Comments on Analysis of Hungarian red deer trophies by means of Principal component analysis in two different counties

Abstract: Authors analyzed data of 9 trophy parameters (weight of the antler, length of main beam, length of brow tine, length of bay tine, length of tray tine, circumference of coronet, lower circumference of main beam, upper circumference of main beam, number of total tines) of 6868 red deer stags shot between 1997 and 2007 and estimated ages were between 4-16 years, from two counties of Hungary (5946 from Somogy and 921 Bács-Kiskun). General linear model was used to evaluate age and "county" effects on the trophy par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In trophy-centric game management the CIC formula is used internationally for evaluating the quality of trophies (CIC: Council for Game and Wildlife Conservation, www.cic-wildlife.org ). The formula comprises qualitative measurements (weight in kg, lengths of main beams, brow and tray tines, circumferences at 3 points on the main beams, spread of the main beams in cm) and qualitative factors (for example, color, beading, shape of the crown); details can be seen, for example, in Bokor et al [ 52 ]. The best trophies gain bronze (above 180 CIC points), silver (above 190 CIC points) or gold medals (“capital” antlers, above 210 CIC points).…”
Section: Methodsmentioning
confidence: 99%
“…In trophy-centric game management the CIC formula is used internationally for evaluating the quality of trophies (CIC: Council for Game and Wildlife Conservation, www.cic-wildlife.org ). The formula comprises qualitative measurements (weight in kg, lengths of main beams, brow and tray tines, circumferences at 3 points on the main beams, spread of the main beams in cm) and qualitative factors (for example, color, beading, shape of the crown); details can be seen, for example, in Bokor et al [ 52 ]. The best trophies gain bronze (above 180 CIC points), silver (above 190 CIC points) or gold medals (“capital” antlers, above 210 CIC points).…”
Section: Methodsmentioning
confidence: 99%
“…Almost all parameters grow together with the age up to 12-14 years. After this period the parameters usually start to decrease slowly (Bokor et al, 2013) (Suttie et al, 1983). Equally, researches of many authors have shown the correlation between development of antler and body mass (Degmečić, 2009).…”
Section: Resultsmentioning
confidence: 99%